Traveloka.com's e-Commerce Service Quality toward Consumer Satisfaction (Case Study: Students at Batanghari University) - Jamira, Anaseputri; Asmas, Denny; Amali, Muhammad (Dinasti Publisher, 2025)
The phenomenon of the development of the tourism sector is claimed to be one of the Strategic Pillars capable of driving the national economy. On the other hand, technological developments in the digital era have given birth to and triggered the development of e-commerce in the tourism sector with the Traveloka.com platform as the champion. Therefore, the purpose of this study is to see how the Quality of Traveloka.com's e-Commerce Services affects User (Consumer) Satisfaction by involving 98 students from Batanghari University (UNBARI) Jambi as respondents. The Combined Research Method was used with Regression analysis tools. The results show that the Quality of Traveloka.com's e-Commerce Services has a positive and significant effect on User Satisfaction. Traveloka.com's e-Commerce Management is expected to improve the performance of the main system, other support systems, and ensure its best performance runs continuously